Effect of steam concentration on char reactivity and structure in the presence/absence of oxygen using Shengli brown coal - Wang, Y.; Chen, X.; Yang, S.; He, X.; Chen, Z.; Zhang, Shu (Elsevier, 2015)
© 2015 Elsevier B.V. Steam-char reactions play a vital role in the gasification process and the presence of oxygen is inevitable in almost all commercial gasifiers. This study aims to investigate the effects of steam concentration on the behavior of Chinese Shengli brown coal gasification in the presence and absence of low concentration of oxygen in a newly-designed drop-tube quartz reactor. Experimental results indicate that the variation in steam concentration had a significant impact on coal conversion, largely depending on reaction temperatures and availability of oxygen. The coal conversion could somehow decrease with increasing steam concentration in the presence of low concentration of oxygen. Meanwhile, the presence of oxygen in the gas has enhanced the Na retention in char probably due to the formation of O-containing compounds or complexes on the char surface. The char structure measured by Raman spectroscopy suggests that the selective consumption of small aromatic ring systems by steam-char reactions was getting less significant when the steam concentration increased to more than 15% by volume. Furthermore, the isothermal reactivities of chars determined by TGA in air imply that the reaction pathways of char-steam and char-oxygen were likely different as the reactivity curves showed totally different shapes.